Drug-induced hyperlactatemia. (14th September 2017) - Blohm, Eike; Lai, Jeffrey; Neavyn, Mark
Abstract: Background: Hyperlactatemia is common in critically ill patients and has a variety of etiologies. Medication toxicity remains an uncommon cause that providers often fail to recognize. In this article, we review several medications that cause hyperlactatemia in either therapeutic or supratherapeutic dosing. When known, the incidence, mortality, pathophysiology, and treatment options are discussed. Methods: We performed a literature search using PUBMED and Google Scholar for English language articles published after 1980 regarding medication induced hyperlactatemia and its management. Our search string resulted in 798 articles of which 138 articles met inclusion criteria and were relevant to the topic of our review. Conclusions: Hyperlactatemia is a relatively rare but life-threatening toxicity of various medication classes. Discontinuation of the drug is always advised, and some toxicities are subject to specific antidotal treatment. If there is no apparent medical cause for hyperlactatemia (sepsis, hypotension, hypoxia), clinicians should consider a toxicological etiology.